Ayurvedic Management of Katishool w.s.r. in Lumbar Spondylosis (AYUSHDHARA, 2024)
Spondylosis refers to degenerative changes in the spine, including the formation of bone spurs and degeneration of intervertebral discs. In Ayurvedic medicine, this condition is comparable to Kati Shool, which is characterized by pain in the lower back (Kati Pradeshe Vedana), restricted mobility (Kriya Sannirodha), and difficulty in ambulation (Gamane Ashaktih). Aim and Objective: This study aims to evaluate the efficacy of Ayurvedic approaches in managing Kati Shool. Methodology: A 56-year-old male patient presented to the Panchakarma outpatient department at the National Institute of Ayurveda, Jaipur, with complaints of lower back pain radiating to the left thigh and leg, persisting for one year. The patient also reported lower back stiffness, numbness, and tingling sensations in both legs over the past ten months. A clinical diagnosis of lumbar spondylosis was established. The patient underwent Shaman Chikitsa for duration of six months, which included a Panchakarma protocol comprising and Kala Basti (Panchtikta Kshir Basti) for 16 days. Results: Significant improvement was observed in the classical signs and symptoms associated with Kati Shool. Discussion and Conclusion: The combination of Panchtikta Kshir Basti and Patra Pinda Swedana, along with appropriate internal medications, demonstrates potential as an effective treatment for Kati Shool in relation to lumbar spondylosis.